Combined treatment (surgery + hormone therapy) of patients with various forms of endometriosis - Mekan R. Orazov; Viktor E. Radzinsky; Evgeny D. Dolgov (LLC "MEDIAFORMAT", 2024)
The global relevance of endometriosis as one of the most common gynaecological nosologies is increasing every year. Currently available evidence-based data help to uncover the most intimate pathogenetic stigmas of the disease and identify key application points for its treatment. That said, the most common forms of endometriosis are currently deep infiltrative, superficial peritoneal, and endometrioid ovarian cysts. This review presents the key pathogenetic mechanisms of different phenotypes of the disease and highlights current strategies for their combined treatment.